2011
DOI: 10.1108/09534811111102328
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming rare listening as a means of organizational re‐enchantment

Abstract: Purpose -The purpose of this paper is to contribute to a reclaiming of the potency of Rogerian listening in organizations. The paper views listening after Rogers, the father of active listening, as a process with potential to re-enchant organizations and the people who comprise them, in a move away from the popular view and professional training that fosters instrumentalized listening that deadens organizations and crushes the spirit of individuals. Design/methodology/approach -The study employs a text analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…That is, merely following instructions to listen in a technical manner, as was carried out in three of our experiments, may not suffice to create psychological safety. Indeed, Tyler () analyzed websites of active‐listening courses intended for business and found that the content of the courses tended to be technical and, hence, dissociated from Rogers's theory. Similarly, Friedman () argued that before effective listening can take place, a person must meditate and relax.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, merely following instructions to listen in a technical manner, as was carried out in three of our experiments, may not suffice to create psychological safety. Indeed, Tyler () analyzed websites of active‐listening courses intended for business and found that the content of the courses tended to be technical and, hence, dissociated from Rogers's theory. Similarly, Friedman () argued that before effective listening can take place, a person must meditate and relax.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a measure based on actual listening behaviors, such as eye contact, is only modestly correlated with the speaker's experience of being listened to (Bodie, Jones, Vickery, Hatcher, & Cannava, ). Moreover, “active listening”—a set of concrete behaviors including reflections of content and emotion—was found to sometimes be perceived as manipulative in the business setting (Tyler, ), and it showed no effect on marital quality (Gottman, Coan, Carrere, & Swanson, ). Therefore, we define listening, in the middle of an abstract‐to‐concrete continuum, as a behavior that manifests the presence of attention, comprehension, and good intention toward the speaker.…”
Section: Listeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizations that want to implement such a work culture should select managers who are truly interested in listening and understand their followers. Listening may afford far more patience than speaking or advising, and followers may quickly notice when leaders' listening is an attempt at mutual understanding or employed as a "technique to manipulate" (Tyler, 2011). In the case of the latter, all attempts and future ones, however honest, may be detrimental to the supervisor-employee relationship.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…When the individual feels accepted and cared for, Rogers argued, mutual understanding and trusting bonds are possible. Hence, in this article, we focus on how the person being listened to perceives the listener (see also Barnlund, 1962; Stone, Patton, & Heen, 1999; Tyler, 2011) and conceptualize listening as a subjective perception of listening quality . Listening quality captures the individual’s perception of being attended to, accepted, and appreciated (Rogers, 1975).…”
Section: Introductionmentioning
confidence: 99%